Identification of Pests and Diseasesof Cocoa Plant (Theobrama Cacao L) and the Level of Attacks in Metun Village - Hariyati, Tati; Putra, Marlan Usmani; Febrianti, Jinni (ITScience (Information Technology and Science), 2025)
This study aims to identify the types of pests and diseases and the attack levels on cocoa plants in Metun Sajau Village. A purposive random sampling method was used, with data collection techniques including field surveys, visual identification of pests and diseases, and recording the intensity and percentage of attacks. The results showed that in Location A, several pests were found: Cocoa Pod Borer (CPB) with an incidence rate of 66.66% and an attack intensity of 35.13%; Helopeltis spp. (76.34%) with an intensity of 34.17%; squirrels (12.72%) with an intensity of 3.3%; and stem/branch borers (1.14%) with an intensity of 0.38%. The disease identified was fruit rot, with an incidence rate of 13.00% and intensity of 2.41%. In Location B, CPB had the highest incidence rate of 79.03% with an attack intensity of 49.34%; Helopeltis spp. (62.25%) with an intensity of 13.69%; squirrels (26.63%) with an intensity of 6.66%; and stem/branch borers (3.50%) with an intensity of 1.16%. Fruit rot disease was also found in Location B, with an incidence rate of 12.17% and intensity of 2.48%. Based on observations at both locations, it can be concluded that Location B has a higher overall pest attack level (76.34%) than Location A (66.66%). These findings provide vital information for developing effective pest and disease management strategies to support sustainable cocoa production.